2023
DOI: 10.1371/journal.pone.0279452
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension and other cardiovascular disease risk factors among university students from the National Polytechnic Institute of Côte d’Ivoire: A cross-sectional study

Abstract: Background Cardiovascular diseases (CVD) are the leading causes of death in the world, mainly occurring in low-and-middle income countries. The aim of this study was to estimate the prevalence of hypertension and other cardiovascular risk factors among university students at a National Polytechnic Institute in Côte d’Ivoire. Methods A cross-sectional study was conducted among students of the National Polytechnic Institute of Côte d’Ivoire. Sample was selected using a non-probabilistic convenient sampling met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
2
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
2
2
3
Order By: Relevance
“…Unlike several previous studies, the associations between high BP and insufficient physical activity, high sodium intake, and low fruit/vegetable consumption were not found in our study [ 22 , 30 , 48 , 49 ]. However, several other studies also did not detect a significant association between them and elevated blood pressure among young students [ 9 , 17 19 , 50 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike several previous studies, the associations between high BP and insufficient physical activity, high sodium intake, and low fruit/vegetable consumption were not found in our study [ 22 , 30 , 48 , 49 ]. However, several other studies also did not detect a significant association between them and elevated blood pressure among young students [ 9 , 17 19 , 50 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, smoking was not significantly associated with high blood pressure in this study after adjusting for confounders. This finding was not comparable to some previous studies [ 22 , 54 ]. However, some other studies showed similar results to our study [ 17 , 19 , 20 , 55 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Com isso, os fatores de risco cardiovascular tem cada vez mais sido identificados nessa população. 8,12 No resgate de evidências científicas re- alizado nesta revisão, identificou-se que os fatores de risco cardiovascular mais encontrados nos universitários, referem-se ao consumo de bebidas alcóolicas, tabagismo, alterações no peso, sedentarismo, aumento de colesterol, estresse, hipertensão arterial e diabetes mellitus. Em estudo realizado entre universitários da Costa do Marfim, verificou-se que 42,5% da amostra referia consumo ativo de álcool e apenas 8% o identificava como um fator de risco para o desenvolvimento de doença cardiovascular.…”
Section: Discussionunclassified
“…NSAIDs have been demonstrated to reduce COX-1 and COX-2 activity, thereby reducing prostaglandin output. Within the first three hours following resistance exercise, prostaglandin activity in injured skeletal muscle tissue peaks, whereas NSAID activity peaks 1-4 hours after consumption 8 .…”
Section: Introductionmentioning
confidence: 99%